DIAGNÓSTICO DO SETOR VAREJISTA NA REGIÃO FRONTEIRA NOROESTE DO RIO GRANDE DO SUL - SPAREMBERGER, ARIOSTO; ZAMBERLAN, LUCIANO; BÜTTENBENDER, PEDRO L.; WAGNER, ADRIANO; KÖHLER, ROMUALDO (Salão do Conhecimento, 2013)
Resumo